Implementation of the Maternal Reflective Method in Inclusive Schools: Teachers' Perspectives on Writing Learning for Deaf Students - Erfin Candra Dwi Hidayat; Pamuji Pamuji; Asri Wijiastuti (Jurnal ORTOPEDAGOGIA, 2025)
This study aims to explore the application of the maternal reflective method in teaching writing for deaf students in inclusive schools. Through a qualitative approach, data were obtained through interviews with three teachers who have experience teaching deaf students at the elementary school level. The findings of the study indicate that these teachers implement the maternal reflective method with various techniques, such as the use of facial expressions, visual media, and word repetition to build deeper understanding. Despite facing challenges related to time constraints in the regular curriculum and lack of understanding from regular teachers, all teachers reported increased student courage in writing as well as a better understanding of sentence structure and self-expression. This study reveals that maternal reflective not only contributes to the development of deaf students' writing skills but also strengthens the emotional relationship between teachers and students, which is an important element in inclusive education. These findings point to the need for systemic support and training for teachers to optimize this approach in inclusive learning.